Single Acceptance Sampling Plan Based on Truncated-life Tests for the Exponentiated Moment Exponential Distribution With Application in Bladder Cancer Data - Zainalabideen AL-Husseini; Mehran Naghizadeh Qomi; Seyed Mohammad Taghi MirMostafaee (علوم بهداشتی ایران, 2023)
Background and Purpose: In statistical quality control, inspecting complete products is very hard due to its cost and time. This research uses a time-truncated single acceptance sampling plan to investigate bladder cancer data for the exponentiated moment exponential distribution. Materials and Methods: A single acceptance sampling plan is used to investigate bladder cancer data when a patient’s remission times following an exponentiated moment exponential distribution. Minimum sample sizes, operating characteristic function, and the associated producer’s risks are obtained and calculated. Results: Minimum sample sizes necessary to ensure a certain mean lifetime for selected acceptance numbers and consumer confidence levels are obtained. The operating characteristic function and the associated producer’s risks are provided. We also analyzed the minimum ratios of the mean life to the specified life. Conclusion: The results show optimal sample sizes decrease when the time to pre-determined mean lifetime ratio increases. Besides, the operating characteristic values of the proposed single sampling plan increase when the ratios of the mean life to the specified life increase.